The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/jhep02(2019)055
|View full text |Cite
|
Sign up to set email alerts
|

Holographic RG flows on curved manifolds and the F-theorem

Abstract: We study F -functions in the context of field theories on S 3 using gaugegravity duality, with the radius of S 3 playing the role of RG scale. We show that the on-shell action, evaluated over a set of holographic RG flow solutions, can be used to define good F -functions, which decrease monotonically along the RG flow from the UV to the IR for a wide range of examples. If the operator perturbing the UV CFT has dimension ∆ > 3/2 these F -functions correspond to an appropriately renormalized free energy. If inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(107 citation statements)
references
References 52 publications
6
97
0
Order By: Relevance
“…The divergent piece of the entanglement entropy satisfies an area law, which prohibits a direct extraction of the IR part of the entropy (see also [46]). It is hence difficult to have a direct interpretation of the entropy of de Sitter itself (see however [62], where a thermodynamic interpretation with a suitable regulated free energy is proposed), but we note that in a theory with dynamical gravity it is conjectured that this entropy is limited by a Bekenstein-Hawking term of A/4G 4 . This entropy, or part thereof, can then potentially be identified with the entanglement entropy whereby 1/G 4 plays the role of the UV cut-off [63].…”
Section: Discussionmentioning
confidence: 89%
“…The divergent piece of the entanglement entropy satisfies an area law, which prohibits a direct extraction of the IR part of the entropy (see also [46]). It is hence difficult to have a direct interpretation of the entropy of de Sitter itself (see however [62], where a thermodynamic interpretation with a suitable regulated free energy is proposed), but we note that in a theory with dynamical gravity it is conjectured that this entropy is limited by a Bekenstein-Hawking term of A/4G 4 . This entropy, or part thereof, can then potentially be identified with the entanglement entropy whereby 1/G 4 plays the role of the UV cut-off [63].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, thanks to the last property in the list above, a DGP‐like mechanism of gravity quasi‐localisation [ 12 ] allows the four‐dimensional observers on the brane to experience ordinary four‐dimensional gravity in a range of scales. In [18] it was shown that the self‐tuning mechanism is robust, in the sense that stabilized solutions with curved branes require a modification of the boundary conditions at the AdS boundary, and therefore belong to a different superselection sector than flat solutions. A dynamical study of this model in the cosmological setting was initiated in [19].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…The expansions for W,S,T for small φ can be found using similar techniques as in [46,47]. The leading terms in this expansion are universal.…”
Section: The Bulk Theory and Its Dual Qftmentioning
confidence: 99%
“…It would be useful to develop more such examples. Finally, it would be interesting to put the Chern-Simons field theory studied in this paper on a 3-sphere and test the recent proposal for the c-function [38].…”
Section: Discussionmentioning
confidence: 98%